ANALISIS LIKUIDITAS, SOLVABILITAS, AKTIVITAS UNTUK MENGUKUR KINERJA KEUANGAN PT. SEKNI INDOTAMA KAB. POLEWALI MANDAR - Rejeki, Sri; Syahrial, Yoppi; Astutik, Wahyuni Sri; Isnaeni, Diana; Naim, Muh. Rezky (JURNAL LENTERA AKUNTANSI, 2023)
The title of this research is about Liquidity Analysis, Solvability, Activity to Measure Financial Performance of PT. Sekni Indotama Kab. Polewali Mandar with the objectives and benefits to describe, analyze, measure financial ratios to financial performance at PT. Telkom Mamuju. This study uses both primary and secondary data based on the company's financial statements PT. Sekni Indotama Kab. Polewali Mandar from 2019 to 2022 and tests were carried out on financial ratios including liquidity ratios, solvency ratios, activity ratios to measure how much financial performance the company PT. Sekni Indotama Kab. Polewali Mandar.As for the results obtained in this study the Financial Performance of PT. Sekni Indotama Kab. Polewali Mandar Based on the results of calculating the liquid ratio analysis, it can be said that Telkom went bankrupt because the company experienced difficulties in paying short -term debt, the Financial Performance of PT. Based on the solvency ratio analysis, Telkom is quite good which continues to grow every year. The reason is the fees obtained from the company's small loans, the Financial Performance of PT. Sekni Indotama Kab. Polewali Mandar uses a fairly healthy performance analysis where it grows every year. This is maintained so that the use of company assets is more efficient and profitable every year. Keywords: Liquidity, Solvency, Activity, Financial Performance